Money and banking in Sierra Leone - Taylor, Alwyn B. (Milan : Finafrica, 1980)
This book examines the nature and operations of financial institutions in Sierra Leone during the period 1960-1976. It also assesses the extent to which the monetary and financial system of Sierra Leone has contributed to the availability of funds for development finance.
Includes bibliographical footnotes
usc 03/08/2017; 30/10/2018
Loans
Keywords: Money; Banks and banking; Economic history; Financial institutions; Sierra Leone